UTILIZATION OF DILATED EYE EXAMS AMONG ADULTS WITH DIABETES - De Lawnia Comer-Ha Gans; Ning Lu; Zo Ramamonjiarivelo (European Scientific Journal, ESJ, 2014)
Purpose: The purpose of this study is to determine the utilization rate of dilated eye exams among adults with diabetes, and to examine the differences in receiving dilated eye exams by predisposing, need, and enabling factors. Methods: National survey data from the 2010 Behavioral Risk Factor Surveillance System. Univariate, weighted bivariate, and logistic regression analyses were performed. Independent variables include demographic information. The dependent variable is the receipt of a dilated eye exam. Results: Some characteristics of individuals who were more likely to receive a dilated eye exam include adults 65 or older, non-Hispanic Blacks, individuals with a health plan, individuals who had a physical exam within the past year, individuals with some type of formal diabetes education, and individuals earning at least $50,000 annually. Conclusion: The Andersen Behavior Model that predisposing, need, and enabling factors are positively associated to the receipt of a dilated eye examination was supported. All enabling factors used in our study are strong predictors of receiving a dilated eye examination. Developing effective recommendations and guidelines for dilated eye exam utilization targeting at-risk adults with diabetes may be beneficial for increasing the number of adults with diabetes who receive annual dilated eye exams.